Equilibrium solubility of carbon dioxide in aqueous N-butyl-3-methylpyridinium tetrafluoroborate, 2-amino-2-methyl-1-propanol and their mixtures / Syamila Nordin - Nordin, Syamila (2016)
There is an urgent need to find a new solvent that has large capacity of absorption, non-corrosive and require low regeneration energy for CO2 capture. One of the promising chemical solvents which had been recognized to execute the task is mixtures of alkanolamines with ionic liquids. The lack of available literature data on the CO2 solubility in the mixture of alkanolamines and ionic liquids, especially pyridinium based ionic liquids leads to the initiation of this research. In this work, CO2 absorption capacity in aqueous 2-amino-2-methyl-I-propanol, (AMP), N-butyl-3methylpyridinium tetralluoroborate. [B3MPYR][BF4] and their mixtures was measured at pressures from 200 kPa up to 5000 kPa and temperatures of 303.15 K 333.15 K. The AMP concentration was maintained at 1 M while the [B3MPYR][BF4] concentration ranges from 0.05 M, 0.1 M, 0.3 M and 1 M. All of the experiments were conducted in a high pressure jacketed reactor. It was found that CO2 loading capacity increases when the pressure increased. Nevertheless, increasing of temperature will decrease the CO2 loading. From the experimental results, it was shown that the aqueous AMP-[B3MPYR][BF4] mixtures have less CO2 absorption capacity compared to single aqueous AMP. In fact, increasing the [B3MPYR][BF4] concentration in the mixtures will decrease the CO2 loading. It was observed that 0.05 M [B3MPYR][BF4] shows the highest CO2 solubility compared to aqueous AMP alone, or aqueous [B3MPYR][BF4] or even in their mixtures of AMP-[B3MPYR][BF4], with CO2 solubility reaching 10.86 mol CO2/mol [B3MPYR][BF4]. A simple correlation, as suggested by Jou and Mather was used to predict the CO2 loading from the experimental results. The predictions of the model were in acceptable agreement with the experimental data where only 16.1% of the overall predicted values deviate more than 20 % compared to the experimental values.